Carrier material and preparation method thereof, catalyst, membrane electrode, fuel cell and electric equipment
By controlling the total oxygen content and pore external oxygen content of the carrier material, the problem of large proton mass transfer resistance of carbon carriers under low humidity conditions is solved, and local flooding is avoided under high humidity and high electrical density conditions, achieving stable performance of fuel cells under different operating conditions.
Patent Information
- Application Number
- CN202510253692.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-05
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-03-05
AI Technical Summary
The existing carbon carrier has a large mass transfer resistance of protons under low humidity conditions, which affects the performance of fuel cells. It is easy to cause local flooding in high humidity and high electrical tight conditions, reducing battery performance.
The carrier material has a total oxygen content of 0.2%-10.0%, and the mass ratio of the pore external oxygen content to the total oxygen content is (0.1-0.5): 1. The hydrophilic properties of the carrier material and the density of oxygen-containing groups in the pore are improved by oxidation treatment.
Improve the proton mass transfer capability of the carrier material under low humidity conditions, avoid local flooding under high humidity and high electrical tight conditions, and ensure the stable performance of the fuel cell under different operating conditions.
Smart Images

Figure CN119764470A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of fuel cell technology, and in particular relates to a carrier material and a preparation method thereof, a catalyst, a membrane electrode, a fuel cell and electrical equipment. Background Art
[0002] A fuel cell is a device that converts chemical energy directly into electrical energy. Its core part is the fuel cell stack, and one of the most important key materials in a fuel cell stack is the carbon carrier. As a porous material, the carbon carrier is mainly used to support catalyst particles. Carbon carriers with large specific surface area and rich pore structure can provide more attachment sites for catalyst particles.
[0003] Carbon carriers generally have pores of different sizes, and catalyst particles are distributed on the surface and in the pores of carbon carriers. The active sites of catalysts on the surface of carbon carriers and in large-sized pores mainly rely on high molecular ionomers with proton transfer and bonding effects for proton transfer, but high molecular ionomers are large in size and not easy to enter the small-sized pores of carbon carriers. Therefore, the active sites of catalysts in small-sized pores mainly rely on water molecules for proton transfer.
[0004] In the related art, under low humidity conditions, the water molecule content in the pores is low, which increases the proton mass transfer resistance in the carbon carrier pores, thereby reducing the proton conductivity of the carbon carrier and affecting the battery performance; in order to improve the proton conductivity of the carbon carrier, the hydrophilicity of the carbon carrier is generally enhanced by increasing the oxygen content of the carbon carrier. The increase in hydrophilicity helps to maintain the wet state of the carbon carrier, thereby reducing the proton mass transfer resistance of the carbon carrier under low humidity conditions. However, although increasing the oxygen content of the carbon carrier is conducive to reducing the proton mass transfer resistance under low humidity conditions, it will also aggravate the local flooding of the carbon carrier under high humidity and high current density conditions, resulting in reduced battery performance. Summary of the invention
[0005] The embodiments of the present invention provide a carrier material and a preparation method thereof, a catalyst, a membrane electrode, a fuel cell and electrical equipment, aiming to solve the aforementioned technical problems.
[0006] In a first aspect, an embodiment of the present invention provides a carrier material suitable for constructing a fuel cell, wherein the carrier material has a plurality of pores; The total oxygen content of the carrier material is Ot, and the mass percentage of Ot in the carrier material is 0.2%-10.0%; The extra-pore oxygen content of the carrier material is Os, and the mass ratio of the Os to the Ot is (0.1-0.5):1.
[0007] In one embodiment, the specific surface area of the carrier material is 200 m 2 / g-1500m 2 / g, preferably, the specific surface area of the carrier material is 500 m 2 / g-1000 m 2 / g; and / or The pores include mesopores, the pore diameter of the mesopores is 2nm-50nm, and the pore volume of the mesopores is 0.4 cm 3 / g-3.0cm 3 / g; and / or The average particle size of the carrier material is 0.2um-3.0um, preferably, the average particle size of the carrier material is 200nm-800nm; and / or The moisture content of the carrier material is less than or equal to 1wt%; and / or In the carrier material, the total content of metal impurities is less than or equal to 1000 ppm, preferably, the metal impurities include metallic iron, and the content of the metallic iron is less than or equal to 50 ppm; and / or The support material includes a porous carbon material having oxygen-containing groups.
[0008] In a second aspect, an embodiment of the present invention provides a method for preparing a carrier material, comprising the following steps: Providing a porous carbon material; The porous carbon material is subjected to oxidation treatment to obtain the carrier material; wherein the carrier material has a plurality of pores; The total oxygen content of the carrier material is Ot, and the mass percentage of Ot in the carrier material is 0.2%-10.0%; The extra-pore oxygen content of the carrier material is Os, and the mass ratio of the Os to the Ot is (0.1-0.5):1.
[0009] In one embodiment, the oxidation treatment step specifically includes: The porous carbon material is subjected to oxygen filling treatment in an oxidizing gas atmosphere to obtain an oxygen-filled material; The oxygen-filled material is subjected to a heat treatment under an inert gas purge to obtain the carrier material.
[0010] In one embodiment, the oxidizing gas comprises oxygen; and / or The gas flow rate of the oxidizing gas is 20 mL / min-40 mL / min; and / or The filling time of the oxygen filling treatment is 0.5h-4h, preferably, the filling time is 2h-3h; and / or The temperature of the oxygen filling treatment is 20°C-30°C; and / or The inert gas comprises nitrogen and / or argon; and / or The gas flow rate of the inert gas is 10 mL / min-50 mL / min, preferably, the gas flow rate of the inert gas is 10 mL / min-30 mL / min; and / or The temperature of the heating treatment is 200°C-500°C; and / or The heating treatment time is 0.5h-2h, preferably, the heating treatment time is 0.5h-1.5h.
[0011] In one embodiment, the oxidation treatment step specifically includes: Dispersing the porous carbon material in a nitric acid solution to obtain a first mixed solution, and drying the first mixed solution at a low temperature to obtain a porous carbon material adsorbed with nitric acid; dispersing the porous carbon material adsorbed with nitric acid in an oxidizing solution to obtain a second mixed solution; The second mixed solution is subjected to heating treatment, washing, and drying to obtain the carrier material.
[0012] In one embodiment, the low temperature drying temperature is 40° C.-80° C.; and / or The concentration of the nitric acid solution is 1.0 mol / L-8.0 mol / L, preferably, the concentration of the nitric acid solution is 2.0 mol / L-4.0 mol / L; and / or The mass percentage of the porous carbon material in the first mixed solution is 20%-60%, preferably, the mass percentage of the porous carbon material in the first mixed solution is 40%-50%; and / or The oxidizing solution comprises at least one of a nitric acid solution, a sulfuric acid solution and a hydrogen peroxide solution. Preferably, the oxidizing solution is a nitric acid solution, and the concentration of the nitric acid solution is 0.2 mol / L-2.0 mol / L; and / or The mass percentage of the porous carbon material adsorbed with nitric acid in the second mixed solution is 0.1%-2.0%, preferably, the mass percentage of the porous carbon material adsorbed with nitric acid in the second mixed solution is 0.5%-1.0%; and / or In the step of heating the second mixed solution, the heating temperature is 70°C-100°C, preferably, the heating temperature is 70°C-80°C, and / or the heating time is 1h-6h, preferably, the heating time is 2h-4h; and / or The step of heating, washing and drying the second mixed solution specifically comprises: heating the second mixed solution to obtain a third mixed solution; Performing solid-liquid separation on the third mixed solution, and washing the product obtained by the solid-liquid separation with water until the pH value is 3-7. Preferably, washing the product obtained by the solid-liquid separation with water until the pH value is 4-6; The washed product is dried to obtain the carrier material, wherein the drying is freeze drying, the freeze drying temperature is -45°C to 0°C, and / or the freeze drying vacuum degree is 0.1Pa-2.5Pa, and / or the freeze drying heating rate is 45°C / min-25°C / min.
[0013] In one embodiment, the oxidation treatment step specifically includes: The porous carbon material is subjected to oxygen filling treatment in an oxidizing gas atmosphere to obtain an oxygen-filled material; Heat-treating the oxygen-filled material under an inert gas purge to obtain an oxygen-containing porous carbon material; Dispersing the oxygen-containing porous carbon material in a nitric acid solution to obtain a first mixture, and drying the first mixture at a low temperature to obtain an oxygen-containing porous carbon material adsorbed with nitric acid; dispersing the oxygen-containing porous carbon material adsorbed with nitric acid in an oxidizing solution to obtain a second mixture; The second mixture is subjected to a heating treatment, washed, and dried to obtain the carrier material.
[0014] In a third aspect, an embodiment of the present invention provides a catalyst, wherein the catalyst includes the carrier material as described above or the carrier material prepared by the method as described above.
[0015] In a fourth aspect, an embodiment of the present invention provides a membrane electrode, which comprises the support material as described above or the support material prepared by the method as described above, or comprises the catalyst as described above.
[0016] In a fifth aspect, an embodiment of the present invention provides a fuel cell, which includes the carrier material as described above or the carrier material prepared by the method as described above, or includes the catalyst as described above, or includes the membrane electrode as described above.
[0017] In a sixth aspect, an embodiment of the present invention provides an electrical-related device, which includes the carrier material as described above or the carrier material prepared by the method as described above, or includes the catalyst as described above, or includes the membrane electrode as described above, or includes the fuel cell as described above.
[0018] Beneficial effects of the embodiments of the present invention: In an embodiment of the present invention, a carrier material suitable for constructing a fuel cell has a plurality of pores, and the plurality of pores can provide attachment sites for metal particles. The total oxygen content of the carrier material is Ot, and the mass percentage of Ot in the carrier material is 0.2%-10.0%; the oxygen content outside the pores of the carrier material is Os, and the mass ratio of Os to Ot is (0.1-0.5): 1. On the one hand, the mass percentage of the total oxygen content Ot of the carrier material in the carrier material is 0.2%-10.0%. Controlling the total oxygen content of the carrier material within the above range can effectively improve the overall hydrophilicity of the carrier material. At the same time, the total oxygen content of the carrier material will not be too high, and the carrier material is not prone to local flooding under high humidity and high electrical density conditions. On the other hand, the total oxygen content of the carrier material is composed of the oxygen content outside the pores Os and the oxygen content inside the pores, and the mass ratio of Os to Ot is (0.1-0.5): 1, which can ensure that the oxygen-containing groups of the carrier material are mainly distributed in the pores. There are more oxygen-containing groups distributed in the pores, which can better improve the hydrophilicity in the pores, so that the carrier material can effectively reduce the proton mass transfer resistance in the pores even under low humidity conditions, thereby ensuring that the carrier material can maintain a good proton mass transfer capacity under low humidity conditions. The embodiments of the present application control the total oxygen content of the carrier material and the oxygen content outside the pores Os and the oxygen content inside the pores of the carrier material, so that the carrier material maintains a good proton mass transfer capacity under low humidity conditions, and is not prone to local flooding under high humidity and high electrical density environments, thereby enabling the fuel cell to have good battery performance regardless of low humidity conditions or high humidity and high electrical density conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the solutions in the present application or the prior art, a brief introduction is given below to the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0020] Figure 1 A preparation flow chart of an embodiment of the carrier material provided in this application; Figure 2 This is a SEM image of the carrier material prepared in Example 1 of the present application; Figure 3 This is the SEM image of the catalyst prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0021] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention. In the present invention, unless otherwise specified, the directional words used, such as "upper" and "lower", generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the drawings; while "inside" and "outside" refer to the outline of the device.
[0022] In the related art, the hydrophilicity of the carbon carrier is generally improved by increasing the total oxygen content of the carbon carrier, thereby reducing the proton mass transfer resistance in the pores of the carbon carrier under low humidity conditions. However, although increasing the total oxygen content of the carbon carrier is beneficial to reducing the proton mass transfer resistance in the pores under low humidity conditions, it will also aggravate the local flooding of the carbon carrier under high humidity and high current density conditions, resulting in a decrease in battery performance, which needs to be further improved.
[0023] To solve the above problems, an embodiment of the present application provides a carrier material suitable for constructing a fuel cell, wherein the carrier material has a plurality of pores; the total oxygen content of the carrier material is Ot, and the mass percentage of Ot in the carrier material is 0.2%-10.0%; the oxygen content outside the pores of the carrier material is Os, and the mass ratio of Os to Ot is (0.1-0.5):1.
[0024] In this embodiment, the oxygen content of the carrier material refers to the mass of oxygen atoms in the oxygen-containing groups on the carrier material; wherein the type of oxygen-containing groups is not limited, and the oxygen-containing groups may be one or more of hydroxyl, carboxyl, carbonyl, ether, phenolic hydroxyl, etc. On the one hand, the total oxygen content Ot of the carrier material has a mass percentage of 0.2%-10.0% in the carrier material. Controlling the total oxygen content of the carrier material within the above range can effectively improve the overall hydrophilicity of the carrier material. At the same time, the total oxygen content of the carrier material will not be too high, and the carrier material is not prone to local flooding under high humidity and high current density conditions. On the other hand, the total oxygen content of the carrier material is composed of the oxygen content outside the pores Os and the oxygen content inside the pores, and the mass ratio of Os to Ot is (0.1-0.5): 1, which can ensure that the oxygen-containing groups of the carrier material are mainly distributed in the pores. There are more oxygen-containing groups distributed in the pores, which can better improve the hydrophilicity in the pores, so that the carrier material can effectively reduce the proton mass transfer resistance in the pores even under low humidity conditions, thereby ensuring that the carrier material can maintain a good proton mass transfer capacity under low humidity conditions. The embodiments of the present application, by controlling the total oxygen content of the carrier material and the oxygen content outside the pores Os and the oxygen content inside the pores of the carrier material, the carrier material maintains a good proton mass transfer capacity under low humidity conditions, and the carrier material is not prone to local flooding in a high humidity and high electrical density environment, thereby enabling the fuel cell to have good battery performance regardless of low humidity conditions or high humidity and high electrical density conditions.
[0025] In this embodiment, the mass percentage of the total oxygen content Ot of the carrier material in the carrier material is 0.2%-10.0%. Optionally, the mass percentage of the oxygen content Ot in the carrier material can be any one of 0.2%, 0.5%, 1.0%, 2.0%, 5.0%, 7.0%, 9.0%, 10.0%, etc., or any range between two of them, which is not limited here. If the mass percentage of the oxygen content Ot in the carrier material is too low, it is easy to cause the hydrophilicity of the carrier material to be poor, and increase the proton mass transfer resistance of the carrier material; if the mass percentage of the oxygen content Ot in the carrier material is too high, it is easy to aggravate the local flooding of the carrier material in a high humidity and high electric density environment, thereby reducing the battery performance.
[0026] In this embodiment, the mass ratio of Os to Ot is (0.1-0.5): 1. Optionally, the mass ratio of Os to Ot can be any one of 0.1: 1, 0.2: 1, 0.3: 1, 0.4: 1, 0.5: 1, etc., or a range between any two of them, which is not limited here. If the mass ratio of Os to Ot is too large, it is easy to cause the oxygen content outside the pores of the carrier material to be too high and the oxygen content in the pores to be too low, and the effect of reducing the proton mass transfer resistance in the pores under low humidity conditions is not ideal; if the mass ratio of Os to Ot is too small, it is easy to cause the oxygen content outside the pores of the carrier material to be too low and the oxygen content in the pores to be too high, and the hydrophilicity of the pores is too strong, which is easy to cause excessive water accumulation in the pores, which is not conducive to the timely discharge of water in the pores and is easy to cause local flooding.
[0027] In one embodiment, the carrier material includes a porous carbon material, and the porous carbon material has an oxygen-containing group. The porous carbon material has a rich pore structure, which can provide more attachment sites for the catalyst particles, making it easy to load the catalyst particles. The porous carbon material has an oxygen-containing group, which can improve the hydrophilicity of the porous carbon material and reduce the proton mass transfer resistance. The type of oxygen-containing group is not limited, and the oxygen-containing group can be one or more of a hydroxyl group, a carboxyl group, a carbonyl group, an ether group, a phenolic hydroxyl group, and the like.
[0028] In one embodiment, the specific surface area of the carrier material is 200 m 2 / g-1500m 2 / g, preferably, the specific surface area of the carrier material is 500 m 2 / g-1000 m 2 In this embodiment, if the specific surface area of the carrier material is less than 200 m 2 / g, which may easily lead to too few attachment sites provided by the carrier material, which is not conducive to the loading of metal particles of the catalyst; if the specific surface area of the carrier material is greater than 1500m 2 / g, which can easily lead to excessive pores in the carrier material and reduce the overall mechanical strength of the carrier material.
[0029] In this embodiment, the specific surface area of the carrier material can be 200m 2 / g、500m 2 / g、700m 2 / g、1000m 2 / g、1200m 2 / g、1500m 2 / g, etc., or the range between any two of them is not limited here.
[0030] In one embodiment, the pores in the carrier material include mesopores, the pore size of the mesopores is 2 nm to 50 nm, and the pore volume of the mesopores is 0.4 cm 3 / g-3.0cm3 Optionally, the pore size of the mesopores can be any one of 2 nm, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, etc. or a range between any two of them, which is not limited here; the pore volume value of the mesopores can be 0.4 cm 3 / g, 0.7cm 3 / g, 1.0 cm 3 / g, 2.0 cm 3 / g, 3.0 cm 3 / g, etc., or any two thereof, are not limited here. In this embodiment, the pore size of the mesopore is 2nm-50nm. The mesopore has a larger space, which can more effectively disperse the metal particles of the catalyst and reduce the agglomeration of the metal particles of the catalyst. In addition, based on the size limitation, the poisoning of the active sites of the catalyst by the ionomer can also be effectively reduced. The pore volume value of the mesopore with a pore size of 2nm-50nm is set at 0.4 cm 3 / g-3.0cm 3 / g range, which can ensure that more precious metal particles are loaded in the mesopores of the carrier material, improve the utilization rate of the metal particles, and at the same time reduce the poisoning effect of the ionomer on the metal particles, thereby improving the battery performance.
[0031] In one embodiment, the average particle size of the carrier material is 0.2um-3.0um, and preferably, the average particle size of the carrier material is 200nm-800nm. Optionally, the average particle size of the carrier material can be any one of 0.2um, 0.5um, 0.8um, 1.0um, 1.5um, 2.0um, 2.5um, 3.0um, etc., or a range between any two of them, which is not limited here. In this embodiment, the average particle size of the carrier material is set to 0.2um-3.0um, and after the carrier material is applied to the membrane electrode, the appearance of large particles in the membrane electrode can be reduced, and the surface flatness of the membrane electrode can be improved.
[0032] In one embodiment, the water content of the carrier material is less than or equal to 1wt%. Because water molecules contain oxygen atoms, when the oxygen content of the carrier material is measured, the water content of the carrier material is less than or equal to 1wt%, which can reduce the influence of water molecules on the measurement results and improve the accuracy of the oxygen content measurement.
[0033] In one embodiment, in the carrier material, the total content of metal impurities is less than or equal to 1000 ppm, preferably, the metal impurities include metallic iron, and the content of metallic iron is less than or equal to 50 ppm. In this embodiment, the total content of metal impurities is less than or equal to 1000 ppm, which can reduce the impact of metal impurities on the accuracy of oxygen content measurement and catalyst performance.
[0034] The present application also provides a method for preparing a carrier material, such as Figure 1 As shown, the following steps are included: S1. providing a porous carbon material; S2, oxidizing the porous carbon material to obtain a carrier material; wherein the carrier material has a plurality of pores; The total oxygen content of the carrier material is Ot, and the mass percentage of Ot in the carrier material is 0.2%-10.0%; The extra-pore oxygen content of the carrier material is Os, and the mass ratio of Os to Ot is (0.1-0.5):1.
[0035] In this embodiment, the porous carbon material is subjected to an oxidation treatment. Through the oxidation treatment, oxygen-containing groups can be introduced into the porous carbon material, thereby obtaining a carrier material with a certain oxygen content.
[0036] In one embodiment, the oxidation treatment step specifically includes: S21, performing oxygen filling treatment on the porous carbon material in an oxidizing gas atmosphere to obtain an oxygen-filled material; S22, heating the oxygen-filled material under inert gas purging to obtain a carrier material.
[0037] In this embodiment, in step S21, the porous carbon material is subjected to oxygen filling treatment in an oxidizing gas atmosphere, so that the oxidizing gas molecules can be adsorbed on the surface and pores of the porous carbon material to obtain an oxygen-filled material. In step S22, the oxygen-filled material is purged with an inert gas, and the inert gas can blow away some of the oxidizing gas molecules on the surface of the oxygen-filled material, thereby regulating the content of the oxidizing gas molecules in the pores of the oxygen-filled material and the content of the oxidizing gas molecules outside the pores; in step S21, the oxidizing gas molecules are not firmly bonded to the porous carbon material, and the oxygen-filled material is heated. The oxidizing gas molecules are easily oxidized with the carbon atoms on the porous carbon at high temperatures, thereby forming oxygen-containing groups on the porous carbon. The oxygen-containing groups can be firmly bonded to the porous carbon through chemical bonds, and the oxygen-containing groups are not easily separated from the porous carbon.
[0038] In one embodiment, the oxidizing gas may include at least one of oxygen, ozone, etc. Preferably, the oxidizing gas is oxygen.
[0039] In one embodiment, the gas flow rate of the oxidizing gas is 20mL / min-40mL / min. Optionally, the gas flow rate of the oxidizing gas can be any one of 20mL / min, 25mL / min, 30mL / min, 35mL / min, 40mL / min, etc. or a range between any two, which is not limited here. In this embodiment, if the gas flow rate of the oxidizing gas is too small, it is easy to cause the amount of oxidizing gas adsorbed on the surface and pores of the porous carbon material to be too small, which in turn causes the amount of oxygen-containing groups formed by the subsequent oxidation reaction to be too small. Ultimately, the oxygen content on the surface and in the pores of the carrier material is too small, which is not conducive to improving the hydrophilicity and proton transfer performance of the carrier material; if the gas flow rate of the oxidizing gas is too large, it is easy to blow away the porous carbon material, and the oxygen filling process cannot be carried out normally.
[0040] In one embodiment, the filling time of the oxygen filling treatment is 0.5h-4h, preferably, the filling time is 2h-3h. Optionally, the filling time of the oxygen filling treatment can be any one of 0.5h, 1h, 2h, 3h, 4h, 0.5h, etc. or the range between any two, which is not limited here. In this embodiment, if the filling time of the oxygen filling treatment is too short, it is easy to cause the amount of oxidizing gas adsorbed on the surface and pores of the porous carbon material to be too small, which in turn causes the amount of oxygen-containing groups formed by the subsequent oxidation reaction to be too small, and finally, the oxygen content on the surface and pores of the carrier material is too small, which is not conducive to improving the hydrophilicity and proton transfer performance in the pores of the carrier material; if the filling time of the oxygen filling treatment is too long, it is easy to cause the amount of oxidizing gas adsorbed on the surface and pores of the porous carbon material to be too much, which in turn causes the oxygen content on the surface and pores of the carrier material to be too much, aggravating the problem of local flooding of the carrier material under high humidity and high electrical density.
[0041] In one embodiment, the temperature of the oxygen filling treatment is 20°C-30°C. Preferably, the temperature of the oxygen filling treatment is any one of 20°C, 22°C, 25°C, 27°C, 30°C, etc., or a range between any two of them, which is not limited here. In this embodiment, the temperature of the oxygen filling treatment is 20°C-30°C. Performing the oxygen filling treatment at a lower temperature can reduce the oxidation reaction between oxygen and the porous carbon material during the oxygen filling treatment stage, prevent the formation of excessive oxygen-containing groups on the surface of the porous carbon material, and facilitate the subsequent further regulation of the oxygen content inside and outside the pores of the carrier material.
[0042] In one embodiment, the inert gas includes nitrogen and / or argon.
[0043] In one embodiment, in step S22, the gas flow rate of the inert gas is 10 mL / min-50 mL / min, preferably, the gas flow rate of the inert gas is 10 mL / min-30 mL / min. Optionally, the gas flow rate of the inert gas can be any one of 10 mL / min, 20 mL / min, 30 mL / min, 40 mL / min, 50 mL / min, etc., or a range between any two thereof, which is not limited here. In this embodiment, if the gas flow rate of the inert gas is too small, it is easy to cause the inert gas to blow away the oxidizing gas on the surface of the porous carbon material. The effect is not ideal, resulting in excessive content of oxidizing gas molecules remaining on the porous carbon material. Ultimately, the content of oxygen-containing groups formed on the surface and in the pores of the carrier material through the oxidation reaction is too high, exacerbating the problem of local flooding of the carrier material under high humidity and high electrical density; if the gas flow rate of the inert gas is too large, it is easy to cause the inert gas to blow away the oxidizing gas on the surface of the porous carbon material while blowing away most of the oxidizing gas in the pores, resulting in the total oxygen content of the carrier material and the oxygen content in the pores being too low, which is not conducive to improving the hydrophilicity and proton transfer performance of the carrier material.
[0044] In one embodiment, in step S22, the temperature of the heat treatment is 200°C-500°C. Optionally, the temperature of the heat treatment can be any one of 200°C, 300°C, 400°C, 500°C, etc. or a range between any two. In this embodiment, if the temperature of the heat treatment is too high, it is easy to cause the structure of the porous carbon material to be destroyed; if the temperature of the heat treatment is too low, it is easy to cause incomplete reaction between the porous carbon material and the oxidizing gas, insufficient introduction of oxygen-containing groups, and too little total oxygen content of the carrier material, which is not conducive to improving the hydrophilicity and proton transfer performance of the carrier material.
[0045] In one embodiment, in step S22, the heating treatment time is 0.5h-2h, preferably, the heating treatment time is 0.5h-1.5h. Optionally, the heating treatment time can be any one of 0.5h, 1h, 1.5h, 2h, etc. or a range between any two. In this embodiment, if the heating treatment time is too long, it is easy to cause the structure of the porous carbon material to be damaged; if the heating treatment time is too short, it is easy to cause incomplete reaction between the porous carbon material and the oxidizing gas, insufficient introduction of oxygen-containing groups, and too little total oxygen content of the carrier material, which is not conducive to improving the hydrophilicity and proton transfer performance of the carrier material.
[0046] In one embodiment, the oxidation treatment step specifically includes: S31, dispersing the porous carbon material in a nitric acid solution to obtain a first mixed solution, and drying the first mixed solution at a low temperature to obtain a porous carbon material adsorbed with nitric acid; S32, dispersing the porous carbon material adsorbed with nitric acid in an oxidizing solution to obtain a second mixed solution; S33, heating the second mixed solution, washing, and drying to obtain a carrier material.
[0047] In this embodiment, the first mixed solution is dried at low temperature. Low temperature drying can reduce the oxidation reaction between nitric acid molecules and the porous carbon material, so that most of the nitric acid molecules can be retained in the porous carbon material, which is beneficial to the subsequent precise control of the content of nitric acid molecules inside and outside the pores of the porous carbon material. During the low-temperature drying process, at the beginning of drying, the water content of the nitric acid solution is relatively high, the concentration of the nitric acid solution is relatively low, and the nitric acid molecules adsorbed on the pore walls and surface of the porous carbon material are relatively small. As the drying proceeds, the water content of the nitric acid solution gradually evaporates, and the nitric acid solution slowly concentrates and gathers in the pores of the porous carbon material. The concentration of the nitric acid solution in the pores increases, so that the amount of nitric acid molecules adsorbed on the pore walls of the porous carbon material is relatively large, while the amount of nitric acid molecules adsorbed on the surface of the porous carbon material is relatively small, thereby regulating the content of nitric acid molecules on the surface and in the pore walls of the porous carbon material; then, the porous carbon material adsorbed with nitric acid is dispersed in an oxidizing solution to obtain a second mixed solution, and the second mixed solution is heated, and the nitric acid molecules on the surface and in the pores of the porous carbon material are easily oxidized with the carbon atoms on the porous carbon at high temperature, thereby forming oxygen-containing groups on the surface and in the pores of the porous carbon material, and the oxygen-containing groups can be firmly combined with carbon atoms through chemical bonds. Therefore, in this embodiment, the content of nitric acid molecules on the pore wall and surface of the porous carbon material is first regulated by a low-temperature drying operation, and then high-temperature heating is performed to allow the nitric acid molecules to undergo an oxidation reaction with the porous carbon material to form oxygen-containing groups on the porous carbon, thereby achieving regulation of the oxygen content inside and outside the pores of the carrier material, so that the carrier material has appropriate oxygen content outside the pores and inside the pores.
[0048] In one embodiment, the temperature of low temperature drying is 40°C-80°C; optionally, the temperature of low temperature drying can be any one of 40°C, 50°C, 60°C, 70°C, 80°C, etc. or a range between any two. In this embodiment, if the temperature of low temperature drying is too low, it is easy to cause the drying efficiency to be too low; if the temperature of low temperature drying is too high, it is easy to cause nitric acid molecules to react with the porous carbon material during the drying process to form too many oxygen-containing groups on the surface of the porous carbon material, which is not conducive to the subsequent precise control of the oxygen content inside and outside the pores of the carrier material.
[0049] In one embodiment, in step S31, the concentration of the nitric acid solution is 1.0mol / L-8.0mol / L, preferably, the concentration of the nitric acid solution is 2.0mol / L-4.0mol / L. Optionally, the concentration of the nitric acid solution can be any one of 1.0mol / L, 2.0mol / L, 4.0mol / L, 6.0mol / L, 8.0mol / L, etc. or a range between any two. In this embodiment, if the concentration of the nitric acid solution is too low, it is easy to cause too little nitric acid molecules adsorbed on the surface and pores of the porous carbon material, which in turn causes the oxygen content on the surface and pores of the carrier material to be too small, which is not conducive to improving the hydrophilicity and proton transfer performance of the carrier material; if the concentration of the nitric acid solution is too high, it is easy to cause too much nitric acid molecules adsorbed on the surface and pores of the porous carbon material, which in turn causes too much oxygen content on the surface and pores of the carrier material, exacerbating the problem of local flooding of the carrier material under high humidity and high electrical density.
[0050] In one embodiment, in step S31, the mass percentage of the porous carbon material in the first mixed solution is 20%-60%. Preferably, the mass percentage of the porous carbon material in the first mixed solution is 40%-50%. Optionally, the mass percentage of the porous carbon material in the first mixed solution can be any one of 20%, 30%, 40%, 50%, 60%, etc. or in the range between any two of them.
[0051] In one embodiment, in step S32, the oxidizing solution includes at least one of a nitric acid solution, a sulfuric acid solution and a hydrogen peroxide solution. Preferably, the oxidizing solution is a nitric acid solution, and the concentration of the nitric acid solution is 0.2 mol / L-2.0 mol / L.
[0052] In one embodiment, in step S32, the mass percentage of the porous carbon material adsorbed with nitric acid in the second mixed solution is 0.1%-2.0%, preferably, the mass percentage of the porous carbon material adsorbed with nitric acid in the second mixed solution is 0.5%-1.0%. Optionally, the mass percentage of the porous carbon material adsorbed with nitric acid in the second mixed solution can be any one of 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, etc., or a range between any two.
[0053] In one embodiment, in step S33, the temperature of the heating treatment is 70°C-100°C, preferably, the temperature of the heating treatment is 70°C-80°C; the time of the heating treatment is 1h-6h, preferably, the time of the heating treatment is 2h-4h. Optionally, the temperature of the heating treatment can be any one of 70°C, 80°C, 90°C, 100°C, etc., or a range between any two thereof; the time of the heating treatment can be any one of 1h, 2h, 3h, 4h, 5h, 6h, etc., or a range between any two thereof.
[0054] In this embodiment, if the temperature of the heating treatment is too high, it is easy to cause the structure of the porous carbon material to be destroyed; if the temperature of the heating treatment is too low, it is easy to cause incomplete reaction between the porous carbon material and the nitric acid molecules, insufficient amount of oxygen-containing groups introduced, and too little total oxygen content of the carrier material, which is not conducive to improving the hydrophilicity and proton transfer performance of the carrier material. If the heating treatment time is too long, it is easy to cause excessive reaction between the porous carbon material and the nitric acid molecules, introduce too many oxygen-containing functional groups, and cause excessive total oxygen content of the carrier material, aggravating the problem of local flooding of the carrier material under high humidity and high electrical density; if the heating treatment time is too short, it is easy to cause incomplete reaction between the porous carbon material and the nitric acid molecules, insufficient amount of oxygen-containing groups introduced, and too little total oxygen content of the carrier material, which is not conducive to improving the hydrophilicity and proton transfer performance of the carrier material.
[0055] In one embodiment, step S33 specifically includes: S331, heating the second mixed solution to obtain a third mixed solution; S332, performing solid-liquid separation on the third mixed solution, and washing the product obtained by the solid-liquid separation with water until the pH value is 3-7. Preferably, washing the product obtained by the solid-liquid separation with water until the pH value is 4-6; S333, drying the washed product to obtain a carrier material.
[0056] In this embodiment, the product obtained by solid-liquid separation is washed with water to remove impurities in the product and improve the purity of the product.
[0057] In this embodiment, the drying is freeze drying, the freeze drying temperature is -45°C to 0°C, the freeze drying vacuum degree is 0.1Pa-2.5Pa, and the freeze drying heating rate is 45°C / min-25°C / min.
[0058] In one embodiment, the oxidation treatment step specifically includes: S41, performing oxygen filling treatment on the porous carbon material in an oxidizing gas atmosphere to obtain an oxygen-filled material; S42, heating the oxygen-filled material under an inert gas purge to obtain an oxygen-containing porous carbon material; S43, dispersing the oxygen-containing porous carbon material in a nitric acid solution to obtain a first mixture, and drying the first mixture at a low temperature to obtain an oxygen-containing porous carbon material adsorbed with nitric acid; S44, dispersing the oxygen-containing porous carbon material adsorbed with nitric acid in an oxidizing solution to obtain a second mixture; S45, heating the second mixture, washing, and drying to obtain a carrier material.
[0059] In this embodiment, an oxygen-containing porous carbon material with a certain oxygen content outside the pores and oxygen content inside the pores is first prepared through steps S41 and S41, and then the oxygen content outside the pores and oxygen content inside the pores of the oxygen-containing porous carbon material are further regulated through steps S43 and S44, so that the oxygen content outside the pores and oxygen content inside the pores of the carrier material can be more accurately regulated.
[0060] The present application also provides a catalyst, which includes the carrier material as described above or the carrier material prepared by the method as described above.
[0061] The present application also provides a method for preparing a catalyst, comprising the following steps: S51, providing a carrier material; S52, dispersing the support material and the metal precursor solution in a reducing agent to obtain a dispersion; S53, adjusting the pH value of the dispersion, heating, filtering, and obtaining a catalyst; Wherein, the carrier material is the carrier material as described above or the carrier material prepared by the method as described above.
[0062] In this embodiment, the metal precursor molecules can be evenly distributed on the surface and pores of the carrier material, and under the action of the reducing agent, the metal precursor molecules can undergo a reduction reaction to generate metal particles in situ on the surface and pores of the carrier material. The carrier material has multiple pores, which can provide attachment sites for metal particles and improve the utilization rate of metal particles. In addition, the total oxygen content Ot of the carrier material has a mass percentage of 0.2%-10.0% in the carrier material. Controlling the total oxygen content of the carrier material within the above range can make the carrier material have moderate hydrophilicity to balance the water management, gas diffusion and proton conduction of the fuel cell. At the same time, it can improve the problem that the carrier material is prone to local flooding in a high humidity and high electrical density environment due to excessive oxygen content. In addition, the total oxygen content of the carrier material is composed of the oxygen content Os outside the pores and the oxygen content inside the pores. The mass ratio of Os to Ot is (0.1-0.5): 1, which can ensure that the pores have a higher oxygen content. There are more oxygen-containing groups distributed in the pores, which can better improve the hydrophilicity of the pores, so that the carrier material can effectively reduce the proton mass transfer resistance in the pores even under low humidity conditions, thereby improving the battery performance of the fuel cell.
[0063] In one embodiment, the mass ratio of the support material to the metal precursor solution is (1-4): 1. Optionally, the mass ratio of the support material to the metal precursor solution is any one of 1:1, 2:1, 3:1, 4:1, etc., or a range between any two of them.
[0064] In one embodiment, the metal precursor solution includes at least one of chloroplatinic acid solution, potassium chloroplatinate solution, potassium chloroplatinite solution, tetraammineplatinum dichloride solution, and di(acetylacetonate)platinum solution.
[0065] In one embodiment, the concentration of the metal precursor solution is 0.1 mol / L-5 mol / L. Preferably, the concentration of the metal precursor solution is 1 mol / L-3 mol / L.
[0066] In one embodiment, the reducing agent includes at least one of formaldehyde, ethylene glycol, sodium borohydride, sodium citrate, sodium hypophosphite, sodium formate, paraformaldehyde, and ascorbic acid.
[0067] In one embodiment, in step S53, the heating temperature is 80°C-150°C, and the heating time is 2h-4h. Optionally, the heating temperature can be any one of 80°C, 90°C, 100°C, 130°C, 150°C, etc., or a range between any two thereof; the heating time can be any one of 2h, 2.5h, 3h, 3.5h, 4h, etc., or a range between any two thereof.
[0068] In one embodiment, step S53 specifically includes: S531, adding an alkaline solution to the dispersion to adjust the pH value of the dispersion, heating, cooling, and obtaining a third mixture, wherein the pH value of the third mixture is 8-14, and preferably, the pH value of the third mixture is 10-12; S532, adding an acidic solution to the third mixture to adjust the pH value of the third mixture, filtering, washing, and drying to obtain a catalyst.
[0069] In this embodiment, the alkaline solution includes at least one of a sodium hydroxide solution and a potassium hydroxide solution, and the concentration of the alkaline solution is 0.5mol / L-2.0mol / L, preferably, the concentration of the alkaline solution is 0.5mol / L-1mol / L. Optionally, the concentration of the alkaline solution can be any one of 0.5mol / L, 0.7mol / L, 1.0mol / L, 1.3mol / L, 1.5mol / L, etc., or a range between any two.
[0070] In this embodiment, the acidic solution includes at least one of hydrochloric acid solution, sulfuric acid solution, and nitric acid solution, and the concentration of the acidic solution is 0.2mol / L-1.0mol / L, preferably, the concentration of the acidic solution is 0.3mol / L-0.6mol / L. Optionally, the concentration of the acidic solution can be any one of 0.2mol / L, 0.4mol / L, 0.6mol / L, 0.8mol / L, 1.0mol / L, etc., or a range between any two.
[0071] In this embodiment, the drying temperature is 60° C.-80° C., and the drying time is 2 h-4 h.
[0072] The present application also provides a membrane electrode, which includes the carrier material as described above or the carrier material prepared by the method as described above, or includes the catalyst as described above.
[0073] The present application also provides a fuel cell, which includes the carrier material as described above or the carrier material prepared by the method as described above, or includes the catalyst as described above, or includes the membrane electrode as described above.
[0074] The present application also provides an electrical device, which includes the carrier material as described above or the carrier material prepared by the method as described above, or includes the catalyst as described above, or includes the membrane electrode as described above, or includes the fuel cell as described above. In this embodiment, the type of the electrical device is not limited, and the electrical device can be a car, a ship, a drone, a fixed power source, a portable power source, etc.
[0075] The present application is further described below through specific embodiments.
[0076] Example 1 (1) placing the porous carbon material in a tube furnace, evacuating the vacuum, and then performing oxygen filling treatment to obtain an oxygen-filled material, wherein the oxygen gas flow rate is 40 mL / min, the oxygen filling time is 4 h, and the oxygen filling temperature is 25 °C; (2) Nitrogen is introduced into the tube furnace for purging and high temperature treatment is performed to obtain a carrier material. The SEM image of the carrier material of this embodiment is shown in FIG. Figure 2 As shown, the nitrogen gas flow rate is 50 mL / min, the high temperature treatment time is 2 h, and the high temperature treatment temperature is 500 ° C. (3) Add 50 mg of the carrier material into ethylene glycol, transfer to a round-bottom flask after ultrasonic dispersion for 1 h, add 1.0 mol / L chloroplatinic acid-ethylene glycol solution dropwise into the round-bottom flask to make the theoretical loading of platinum metal 50%, stir evenly, and obtain a dispersion; (4) 1.0 mol / L NaOH-ethylene glycol solution was added dropwise to the dispersion to adjust the pH of the solution in the round-bottom flask to 12. Subsequently, the round-bottom flask was placed in an oil bath and heated under reflux at 140°C for 2 h. After the reaction was completed, it was naturally cooled to room temperature. 0.5 mol / L nitric acid solution was added dropwise under stirring to adjust the pH of the solution in the round-bottom flask to 2.0. After filtering and washing, the sample was placed in a vacuum oven and dried at 60°C for 4 h to obtain a catalyst. The SEM image of the catalyst in this embodiment is shown in FIG. Figure 3 shown.
[0077] Example 2 (1) placing the porous carbon material in a tube furnace, evacuating the vacuum, and then performing oxygen filling treatment to obtain an oxygen-filled material, wherein the oxygen gas flow rate is 40 mL / min, the filling time is 4 h, and the oxygen filling temperature is 25 °C; (2) introducing nitrogen gas into the tubular furnace for purging and simultaneously performing high temperature treatment to obtain a carrier material, wherein the nitrogen gas flow rate is 10 mL / min, the high temperature treatment time is 2 h, and the high temperature treatment temperature is 500° C.; (3) Add 50 mg of the carrier material into ethylene glycol, transfer to a round-bottom flask after ultrasonic dispersion for 1 h, add 1.0 mol / L chloroplatinic acid-ethylene glycol solution dropwise into the round-bottom flask to make the theoretical loading of platinum metal 50%, stir evenly, and obtain a dispersion; (4) 1.0 mol / L NaOH-ethylene glycol solution was added dropwise to the dispersion to adjust the pH value of the solution in the round-bottom flask to 12. Subsequently, the round-bottom flask was placed in an oil bath and heated under reflux at 140°C for 2 h. After the reaction was completed, the mixture was naturally cooled to room temperature. 0.5 mol / L nitric acid solution was added dropwise under stirring to adjust the pH value of the solution in the round-bottom flask to 2.0. After filtering and washing, the sample was placed in a vacuum oven and dried at 60°C for 4 h to obtain the catalyst.
[0078] Example 3 (1) placing the porous carbon material in a tube furnace, evacuating the vacuum, and then performing oxygen filling treatment to obtain an oxygen-filled material, wherein the oxygen gas flow rate is 20 mL / min, the filling time is 0.5 h, and the oxygen filling temperature is 25 °C; (2) introducing nitrogen gas into the tubular furnace for purging and simultaneously subjecting the material to high temperature treatment to obtain a carrier material, wherein the nitrogen gas flow rate is 50 mL / min, the high temperature treatment time is 0.5 h, and the high temperature treatment temperature is 200° C.; (3) Add 50 mg of the carrier material into ethylene glycol, transfer to a round-bottom flask after ultrasonic dispersion for 1 h, add 1.0 mol / L chloroplatinic acid-ethylene glycol solution dropwise into the round-bottom flask to make the theoretical loading of platinum metal 50%, stir evenly, and obtain a dispersion; (4) 1.0 mol / L NaOH-ethylene glycol solution was added dropwise to the dispersion to adjust the pH value of the solution in the round-bottom flask to 12. Subsequently, the round-bottom flask was placed in an oil bath and heated under reflux at 140°C for 2 h. After the reaction was completed, the mixture was naturally cooled to room temperature. 0.5 mol / L nitric acid solution was added dropwise under stirring to adjust the pH value of the solution in the round-bottom flask to 2.0. After filtering and washing, the sample was placed in a vacuum oven and dried at 60°C for 4 h to obtain the catalyst.
[0079] Example 4 The difference between Example 4 and Example 1 is that: In step (1), the oxygen gas flow rate is 20 mL / min; the rest is the same as in Example 1.
[0080] Example 5 The difference between Example 5 and Example 1 is that: In step (1), the oxygen filling time is 0.5 h; the rest is the same as in Example 1.
[0081] Example 6 The difference between Example 6 and Example 1 is that: In step (2), the nitrogen gas flow rate is 10 mL / min; the rest is the same as in Example 1.
[0082] Example 7 The difference between Example 7 and Example 1 is that: In step (2), the high temperature treatment time is 0.5 h; the rest is the same as in Example 1.
[0083] Example 8 The difference between Example 8 and Example 1 is that: In step (2), the high temperature treatment temperature is 200°C; the rest is the same as in Example 1.
[0084] Example 9 (1) dispersing the porous carbon material in a 4.0 mol / L nitric acid solution to obtain a first mixed solution, stirring and drying the first mixed solution at 50° C. to obtain a porous carbon material adsorbed with nitric acid, wherein the mass percentage of the porous carbon material in the first mixed solution is 40%; (2) adding the porous carbon material adsorbed with nitric acid into deionized water to prepare a carbon slurry with a mass percentage of 2.0%, and dissolving the carbon slurry in 2.0 mol / L dilute nitric acid to obtain a mixed solution; (3) The mixed solution was placed in a water bath at 80°C and heated for 4 h. After the heating was completed, the solid-liquid separation was performed. The product obtained by the solid-liquid separation was washed with water until the pH value of the supernatant reached 4.0. Finally, the filtrate was placed in a freeze dryer for drying to obtain a carrier material. (4) Add 50 mg of the carrier material to ethylene glycol, transfer to a round-bottom flask after ultrasonic dispersion for 1 h, add 1.0 mol / L chloroplatinic acid-ethylene glycol solution dropwise to the round-bottom flask to make the theoretical loading of platinum metal 50%, stir evenly, and obtain a dispersion; (5) 1.0 mol / L NaOH-ethylene glycol solution was added dropwise to the dispersion to adjust the pH value of the solution in the round-bottom flask to 12. Subsequently, the round-bottom flask was placed in an oil bath and heated under reflux at 140 °C for 2 h. After the reaction was completed, the mixture was naturally cooled to room temperature. 0.5 mol / L nitric acid solution was added dropwise under stirring to adjust the pH value of the solution in the round-bottom flask to 2.0. After filtering and washing, the sample was placed in a vacuum oven and dried at 60 °C for 4 h to obtain the catalyst.
[0085] Example 10 (1) dispersing the porous carbon material in an 8.0 mol / L nitric acid solution to obtain a first mixed solution, stirring and drying the first mixed solution at 80° C. to obtain a porous carbon material adsorbed with nitric acid, wherein the mass percentage of the porous carbon material in the first mixed solution is 20%; (2) adding the porous carbon material adsorbed with nitric acid into deionized water to prepare a carbon slurry with a mass percentage of 2.0%, and dissolving the carbon slurry in 2.0 mol / L dilute nitric acid to obtain a mixed solution; (3) The mixed solution was placed in a 100°C water bath and heated for 6 h. After the heating was completed, the solid-liquid separation was performed. The product obtained by the solid-liquid separation was washed with water until the pH value of the supernatant reached 4.0. Finally, the filtrate was placed in a freeze dryer for drying to obtain a carrier material. (4) Add 50 mg of the carrier material to ethylene glycol, transfer to a round-bottom flask after ultrasonic dispersion for 1 h, add 1.0 mol / L chloroplatinic acid-ethylene glycol solution dropwise to the round-bottom flask to make the theoretical loading of platinum metal 50%, stir evenly, and obtain a dispersion; (5) 1.0 mol / L NaOH-ethylene glycol solution was added dropwise to the dispersion to adjust the pH value of the solution in the round-bottom flask to 12. Subsequently, the round-bottom flask was placed in an oil bath and heated under reflux at 140 °C for 2 h. After the reaction was completed, the mixture was naturally cooled to room temperature. 0.5 mol / L nitric acid solution was added dropwise under stirring to adjust the pH value of the solution in the round-bottom flask to 2.0. After filtering and washing, the sample was placed in a vacuum oven and dried at 60 °C for 4 h to obtain the catalyst.
[0086] Embodiment 11 (1) dispersing the porous carbon material in a 1.0 mol / L nitric acid solution to obtain a first mixed solution, stirring and drying the first mixed solution at 40° C. to obtain a porous carbon material adsorbed with nitric acid, wherein the mass percentage of the porous carbon material in the first mixed solution is 60%; (2) adding the porous carbon material adsorbed with nitric acid into deionized water to prepare a carbon slurry with a mass percentage of 2.0%, and dissolving the carbon slurry in 2.0 mol / L dilute nitric acid to obtain a mixed solution; (3) The mixed solution was placed in a 70°C water bath and heated for 1 h. After the heating was completed, the solid-liquid separation was performed. The product obtained by the solid-liquid separation was washed with water until the pH value of the supernatant reached 4.0. Finally, the filtrate was placed in a freeze dryer for drying to obtain a carrier material. (4) Add 50 mg of the carrier material to ethylene glycol, transfer to a round-bottom flask after ultrasonic dispersion for 1 h, add 1.0 mol / L chloroplatinic acid-ethylene glycol solution dropwise to the round-bottom flask to make the theoretical loading of platinum metal 50%, stir evenly, and obtain a dispersion; (5) 1.0 mol / L NaOH-ethylene glycol solution was added dropwise to the dispersion to adjust the pH value of the solution in the round-bottom flask to 12. Subsequently, the round-bottom flask was placed in an oil bath and heated under reflux at 140 °C for 2 h. After the reaction was completed, the mixture was naturally cooled to room temperature. 0.5 mol / L nitric acid solution was added dropwise under stirring to adjust the pH value of the solution in the round-bottom flask to 2.0. After filtering and washing, the sample was placed in a vacuum oven and dried at 60 °C for 4 h to obtain the catalyst.
[0087] Example 12 (1) placing the porous carbon material in a tube furnace, evacuating the vacuum, and then performing oxygen filling treatment to obtain an oxygen-filled material, wherein the oxygen gas flow rate is 30 mL / min, the filling time is 3 h, and the oxygen filling temperature is 25 °C; (2) introducing nitrogen gas into the tubular furnace for purging and simultaneously subjecting the material to high temperature treatment to obtain an oxygen-containing porous carbon material, wherein the nitrogen gas flow rate is 20 mL / min, the high temperature treatment time is 1 h, and the high temperature treatment temperature is 300 °C; (3) dispersing the oxygen-containing porous carbon material in a 4.0 mol / L nitric acid solution to obtain a first mixed solution, stirring and drying the first mixed solution at 50° C. to obtain a porous carbon material adsorbed with nitric acid, wherein the mass percentage of the porous carbon material in the first mixed solution is 40%; (4) adding the porous carbon material adsorbed with nitric acid into deionized water to prepare a carbon slurry with a mass percentage of 2.0%, and dissolving the carbon slurry in 2.0 mol / L dilute nitric acid to obtain a mixed solution; (5) The mixed solution was placed in a water bath at 80°C and heated for 4 h. After the heating was completed, the solid-liquid separation was performed. The product obtained by the solid-liquid separation was washed with water until the pH value of the supernatant reached 4.0. Finally, the filtrate was placed in a freeze dryer for drying to obtain a carrier material. (6) Add 50 mg of the carrier material to ethylene glycol, and transfer to a round-bottom flask after ultrasonic dispersion for 1 h. Add 1.0 mol / L chloroplatinic acid-ethylene glycol solution to the round-bottom flask to make the theoretical loading of platinum metal 50%. Stir evenly to obtain a dispersion. (7) 1.0 mol / L NaOH-ethylene glycol solution was added dropwise to the dispersion to adjust the pH value of the solution in the round-bottom flask to 12. Subsequently, the round-bottom flask was placed in an oil bath and heated under reflux at 140 °C for 2 h. After the reaction was completed, the mixture was naturally cooled to room temperature. 0.5 mol / L nitric acid solution was added dropwise under stirring to adjust the pH value of the solution in the round-bottom flask to 2.0. After filtering and washing, the sample was placed in a vacuum oven and dried at 60 °C for 4 h to obtain the catalyst.
[0088] Comparative Example 1 (1) placing the porous carbon material in a tube furnace, evacuating the vacuum, introducing nitrogen into the tube furnace for purging, and simultaneously subjecting the material to high temperature treatment to obtain a carrier material, wherein the nitrogen gas flow rate is 50 mL / min, the high temperature treatment time is 2 h, and the high temperature treatment temperature is 500 °C; (2) Add 50 mg of the carrier material to ethylene glycol, transfer to a round-bottom flask after ultrasonic dispersion for 1 h, add dropwise 1.0 mol / L chloroplatinic acid-ethylene glycol solution to the round-bottom flask to make the theoretical loading of platinum metal 50%, stir evenly, and obtain a dispersion; (3) 1.0 mol / L NaOH-ethylene glycol solution was added dropwise to the dispersion to adjust the pH value of the solution in the round-bottom flask to 12. Subsequently, the round-bottom flask was placed in an oil bath and heated under reflux at 140°C for 2 h. After the reaction was completed, the mixture was naturally cooled to room temperature. 0.5 mol / L nitric acid solution was added dropwise under stirring to adjust the pH value of the solution in the round-bottom flask to 2.0. After filtering and washing, the sample was placed in a vacuum oven and dried at 60°C for 4 h to obtain the catalyst.
[0089] Comparative Example 2 (1) dispersing the porous carbon material in an 8.0 mol / L nitric acid solution to obtain a first mixed solution, stirring and drying the first mixed solution at 40° C. to obtain a porous carbon material adsorbed with nitric acid, wherein the mass percentage of the porous carbon material in the first mixed solution is 40%; (2) washing the porous carbon material adsorbed with nitric acid with water until the pH value of the supernatant reaches 4.0, and finally, placing the filtrate into a freeze dryer for drying to obtain a carrier material; (3) Add 50 mg of the carrier material into ethylene glycol, transfer to a round-bottom flask after ultrasonic dispersion for 1 h, add 1.0 mol / L chloroplatinic acid-ethylene glycol solution dropwise into the round-bottom flask to make the theoretical loading of platinum metal 50%, stir evenly, and obtain a dispersion; (4) 1.0 mol / L NaOH-ethylene glycol solution was added dropwise to the dispersion to adjust the pH value of the solution in the round-bottom flask to 12. Subsequently, the round-bottom flask was placed in an oil bath and heated under reflux at 140°C for 2 h. After the reaction was completed, the mixture was naturally cooled to room temperature. 0.5 mol / L nitric acid solution was added dropwise under stirring to adjust the pH value of the solution in the round-bottom flask to 2.0. After filtering and washing, the sample was placed in a vacuum oven and dried at 60°C for 4 h to obtain the catalyst.
[0090] Comparative Example 3 The difference between Comparative Example 3 and Example 3 is that: In step (1), the oxygen gas flow rate is 5 mL / min; the rest is the same as in Example 3.
[0091] Comparative Example 4 The difference between Comparative Example 4 and Example 3 is that: In step (2), the high temperature treatment time is 0.2 h; the rest is the same as in Example 3.
[0092] Comparative Example 5 The difference between Comparative Example 5 and Example 2 is that: In step (1), the oxygen filling time is 6 hours; the rest is the same as in Example 2.
[0093] Comparative Example 6 The difference between Comparative Example 6 and Example 3 is that: In step (2), the high temperature treatment temperature is 50°C; the rest is the same as in Example 3.
[0094] Comparative Example 7 The difference between Comparative Example 7 and Example 2 is that: In step (2), the high temperature treatment temperature is 800°C; the rest is the same as in Example 2.
[0095] Comparative Example 8 The difference between Comparative Example 8 and Example 3 is that: In step (2), the nitrogen gas flow rate is 5 ml / min; the rest is the same as in Example 3.
[0096] Comparative Example 9 (1) placing the porous carbon material in a tube furnace, evacuating the vacuum, and then performing oxygen filling treatment to obtain an oxygen-filled material, wherein the oxygen gas flow rate is 20 mL / min, the filling time is 0.5 h, and the oxygen filling temperature is 25 °C; (2) subjecting the oxygen-filled material to high-temperature treatment to obtain a carrier material, wherein the high-temperature treatment time is 0.5 h and the high-temperature treatment temperature is 200° C.; (3) Add 50 mg of the carrier material into ethylene glycol, transfer to a round-bottom flask after ultrasonic dispersion for 1 h, add 1.0 mol / L chloroplatinic acid-ethylene glycol solution dropwise into the round-bottom flask to make the theoretical loading of platinum metal 50%, stir evenly, and obtain a dispersion; (4) 1.0 mol / L NaOH-ethylene glycol solution was added dropwise to the dispersion to adjust the pH value of the solution in the round-bottom flask to 12. Subsequently, the round-bottom flask was placed in an oil bath and heated under reflux at 140°C for 2 h. After the reaction was completed, the mixture was naturally cooled to room temperature. 0.5 mol / L nitric acid solution was added dropwise under stirring to adjust the pH value of the solution in the round-bottom flask to 2.0. After filtering and washing, the sample was placed in a vacuum oven and dried at 60°C for 4 h to obtain the catalyst.
[0097] Comparative Example 10 The difference between Comparative Example 10 and Example 11 is: In step (3), the water bath heating temperature is 30°C, and the rest is the same as in Example 11.
[0098] Comparative Example 11 The difference between Comparative Example 11 and Example 10 is that: In step (3), the water bath heating temperature is 120°C, and the rest is the same as in Example 10.
[0099] Comparative Example 12 The difference between Comparative Example 12 and Example 11 is that: In step (3), the water bath heating time is 0.5 h, and the rest is the same as in Example 11.
[0100] Comparative Example 13 The difference between Comparative Example 13 and Example 10 is that: In step (3), the water bath heating time is 15 h, and the rest is the same as in Example 10.
[0101] Comparative Example 14 The difference between Comparative Example 14 and Example 11 is that: In step (1), the concentration of the nitric acid solution is 0.5 mol / L; the rest is the same as in Example 11.
[0102] Comparative Example 15 The difference between Comparative Example 15 and Example 10 is that: In step (1), the concentration of the nitric acid solution is 10.0 mol / L; the rest is the same as in Example 10.
[0103] Comparative Example 16 The difference between Comparative Example 16 and Example 11 is: Step (1) is: dispersing the porous carbon material in a 1.0 mol / L nitric acid solution to obtain a first mixed solution, stirring and drying the first mixed solution at 100° C. to obtain a porous carbon material adsorbed with nitric acid, wherein the mass percentage of the porous carbon material in the first mixed solution is 60%; The rest is the same as Example 11.
[0104] Comparative Example 17 (1) dispersing the porous carbon material in a 1.0 mol / L nitric acid solution to obtain a first mixed solution, wherein the mass percentage of the porous carbon material in the first mixed solution is 60%; (2) placing the first mixed solution in a 70° C. water bath and heating it for 1 h. After the heating is completed, the solid-liquid separation is performed. The product obtained by the solid-liquid separation is washed with water until the pH value of the supernatant reaches 4.0. Finally, the filtrate is placed in a freeze dryer for drying to obtain a carrier material. (3) Add 50 mg of the carrier material into ethylene glycol, transfer to a round-bottom flask after ultrasonic dispersion for 1 h, add 1.0 mol / L chloroplatinic acid-ethylene glycol solution dropwise into the round-bottom flask to make the theoretical loading of platinum metal 50%, stir evenly, and obtain a dispersion; (4) 1.0 mol / L NaOH-ethylene glycol solution was added dropwise to the dispersion to adjust the pH value of the solution in the round-bottom flask to 12. Subsequently, the round-bottom flask was placed in an oil bath and heated under reflux at 140°C for 2 h. After the reaction was completed, the mixture was naturally cooled to room temperature. 0.5 mol / L nitric acid solution was added dropwise under stirring to adjust the pH value of the solution in the round-bottom flask to 2.0. After filtering and washing, the sample was placed in a vacuum oven and dried at 60°C for 4 h to obtain the catalyst.
[0105] Test Method The following tests were performed on the carrier materials prepared in Examples 1 to 12 and Comparative Examples 1 to 17: 1. Test of oxygen content (Os) outside the pores of carrier materials: The test method is: weigh 10 mg of the carrier material and use a SEM electron spectrometer (SEM-EDS) to measure the oxygen content Os on the surface of the carrier material.
[0106] (II) Test of total oxygen content (Ot) of carrier materials: The test method is: Weigh 1.2g of carrier material and spread it flat in the moisture meter, heat it at 150℃ for 6min, then take 50mg of the dried carrier material in a glass bottle for sample testing, and dry it again before testing (120℃, 30min). The carrier material and the co-solvent are added to the graphite crucible and heated to a maximum of 3000℃ to melt, releasing CO and CO2. CO is oxidized to CO2 by rare earth copper oxide, and CO2 is measured by an infrared detection cell. In addition, X-rays are used to act on the surface of the dried carrier material to generate photoelectrons. The photoelectron energy spectrum is obtained by analyzing the energy distribution of the photoelectrons. It is used to study the total oxygen content (Ot) of the carrier material.
[0107] The test results are shown in Table 1 below: Table 1
[0108] The catalysts prepared in Examples 1 to 12 and Comparative Examples 1 to 17 were prepared into membrane electrodes, which were assembled into fuel cells. The fuel cells were tested for voltage output using a fuel cell measuring device: (III) Performance test under low humidification conditions: Test method: Check the connection status of the fuel cell to ensure that the gas, liquid and electrical connections are leak-free and correctly connected. Start the test bench, first introduce nitrogen for preheating, set the battery test temperature to 80°C and humidity to 100%RH, and after the battery temperature and humidity are stable, introduce H2 to the anode and air to the cathode, and start activation from the open circuit state. The battery is usually operated in constant current mode, and the activation is terminated when the battery voltage fluctuation is less than ±5mV. After the activation is completed, start the single cell test: the battery temperature is set to 80°C, the anode and cathode are supplied with air (500sccm) and H2 (500sccm) with a humidity of 50%RH respectively, the anode and cathode back pressure is set to 150kPa, and the load is increased to record the battery at 1A / cm 2 The output voltage under.
[0109] (IV) Performance test under high humidification conditions: Test method: Check the connection status of the fuel cell to ensure that the gas, liquid and electrical connections are leak-free and correctly connected. Start the test bench, first introduce nitrogen for preheating, set the battery test temperature to 80°C and humidity to 100%RH, and after the battery temperature and humidity are stable, introduce H2 to the anode and air to the cathode, and start activation from the open circuit state. The battery is usually operated in constant current mode, and activation is terminated when the battery voltage fluctuation is less than ±5mV. After activation, start the single cell test: the battery temperature is set to 80°C, the anode and cathode are supplied with air (500sccm) and H2 (500sccm) with a humidity of 100%RH respectively, the anode and cathode back pressure is set to 150kPa, and the load is increased to record the battery at 2A / cm2 The output voltage under.
[0110] The test results are shown in Table 2 below: Table 2
[0111] From the analysis of Examples 1 to 4 and Comparative Example 3, it can be seen that when performing oxygen filling treatment, the oxygen gas flow rate is controlled within an appropriate range, further ensuring that the oxygen content of the carrier material is controlled within an appropriate range. While improving the hydrophilicity and proton transfer performance of the carrier material, it can also improve the problem of local flooding of the carrier material under high humidity and high current density, thereby improving battery performance.
[0112] From the analysis of Examples 1 to 3, Example 5 and Comparative Example 5, it can be seen that when performing oxygen filling treatment, controlling the oxygen filling time within an appropriate range can further ensure that the oxygen content of the carrier material is controlled within an appropriate range. While improving the hydrophilicity and proton transfer performance of the carrier material, it can also improve the problem of local flooding of the carrier material under high humidity and high current density, thereby improving battery performance.
[0113] From the analysis of Examples 1 to 3, Example 6, Comparative Example 8 and Comparative Example 9, it can be known that by performing nitrogen purging during high-temperature oxidation and controlling the gas flow rate of nitrogen within an appropriate range, while ensuring that the total oxygen content of the carrier material is controlled within an appropriate range, the oxygen content in the pores and the oxygen content outside the pores of the carrier material can be regulated to ensure that more oxygen-containing groups are distributed in the pores of the carrier material, which can better improve the hydrophilicity of the pores, so that the carrier material can maintain a good proton mass transfer ability under low humidity conditions, and is not prone to local flooding under high humidity and high current density, thereby making the fuel cell have good battery performance regardless of whether it is under low humidity conditions or high humidity and high current density conditions.
[0114] From the analysis of Examples 1 to 3, Example 7, Comparative Example 1 and Comparative Example 4, it can be seen that by subjecting the oxygen-filled material to high-temperature oxidation and controlling the high-temperature oxidation time within an appropriate range, the oxygen-containing groups can be firmly fixed on the carrier material and the carrier material can have a suitable oxygen content. While improving the hydrophilicity and proton transfer performance of the carrier material, it can also improve the problem of local flooding of the carrier material under high humidity and high current density, thereby improving battery performance.
[0115] From the analysis of Examples 1 to 3, Example 8, Comparative Example 1 and Comparative Example 6, it can be seen that by subjecting the oxygen-filled material to high-temperature oxidation and controlling the temperature of the high-temperature oxidation within an appropriate range, the carrier material can have a suitable oxygen content, while reducing the damage to the structure of the porous carbon material caused by high-temperature treatment. While improving the hydrophilicity and proton transfer performance of the carrier material, it can also improve the problem of local flooding of the carrier material under high humidity and high current density, thereby improving battery performance.
[0116] From the analysis of Examples 9 to 12, Comparative Example 16 and Comparative Example 17, it can be known that the first mixed solution containing the porous carbon material and the nitric acid solution is subjected to low-temperature drying, and the temperature of the low-temperature drying is controlled within an appropriate range. Low-temperature drying can reduce the oxidation reaction between the nitric acid solution and the porous carbon material, so that most of the nitric acid molecules can be retained in the porous carbon material. At the same time, the content of nitric acid molecules on the surface and in the pore walls of the porous carbon material can be accurately regulated to ensure that more oxygen-containing groups are distributed in the pores of the carrier material, which can better improve the hydrophilicity of the pores, so that the carrier material can maintain a good proton mass transfer ability under low humidity conditions, and is not prone to local flooding under high humidity and high current density, thereby making the fuel cell have good battery performance regardless of whether it is under low humidity conditions or high humidity and high current density conditions.
[0117] From the analysis of Example 9 to Example 12, Comparative Example 14, Comparative Example 15 and Comparative Example 17, it can be known that the first mixed solution containing the porous carbon material and the nitric acid solution is dried at low temperature, and the concentration of the nitric acid solution is controlled within an appropriate range. Low-temperature drying can accurately regulate the content of nitric acid molecules on the surface of the porous carbon material and in the pore wall, ensuring that there are more oxygen-containing groups distributed in the pores of the carrier material, which can better improve the hydrophilicity of the pores, so that the carrier material can maintain a good proton mass transfer capacity under low humidity conditions; the concentration of nitric acid is controlled within an appropriate range, so that the carrier material has a suitable oxygen content, while improving the hydrophilicity and proton transfer performance of the carrier material, it can reduce the problem of local flooding of the carrier material under high humidity and high electrical density, thereby making the fuel cell have good battery performance regardless of whether it is under low humidity conditions or under high humidity and high electrical density conditions.
[0118] From the analysis of Examples 9 to 12, Comparative Example 2, Comparative Example 10 and Comparative Example 11, it can be seen that by heating the porous carbon material adsorbed with nitric acid molecules in a water bath and controlling the water bath heating temperature within an appropriate range, the oxygen-containing groups can be firmly fixed on the carrier material, reducing the damage to the structure of the porous carbon material caused by high temperature, and at the same time allowing the carrier material to have a suitable oxygen content.
[0119] From the analysis of Examples 9 to 12, Comparative Example 2, Comparative Example 12 and Comparative Example 13, it can be known that heating the porous carbon material adsorbed with nitric acid molecules in a water bath and controlling the water bath heating time within an appropriate range can further ensure that the oxygen content of the carrier material is controlled within an appropriate range, thereby improving the hydrophilicity and proton transfer performance of the carrier material, while improving the problem of local flooding of the carrier material under high humidity and high current density, thereby improving battery performance.
[0120] The embodiments of the present invention are described in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A carrier material suitable for constructing a fuel cell, characterized in that: The carrier material has a plurality of pores; The total oxygen content of the carrier material is Ot, and the mass percentage of Ot in the carrier material is 0.2%-10.0%; The extra-pore oxygen content of the carrier material is Os, and the mass ratio of the Os to the Ot is (0.1-0.5):
1.
2. The carrier material according to claim 1, characterized in that The specific surface area of the carrier material is 200 m 2 / g-1500m 2 / g; and / or The pores include mesopores, the pore diameter of the mesopores is 2nm-50nm, and the pore volume of the mesopores is 0.4 cm 3 / g-3.0cm 3 / g; and / or The average particle size of the carrier material is 0.2um-3.0um; and / or The moisture content of the carrier material is less than or equal to 1wt%; and / or In the carrier material, the total content of metal impurities is less than or equal to 1000 ppm; and / or The support material includes a porous carbon material having oxygen-containing groups.
3. The carrier material according to claim 2, characterized in that The specific surface area of the carrier material is 500 m 2 / g-1000 m 2 / g; and / or The average particle size of the carrier material is 200nm-800nm; and / or The metal impurities include metallic iron, and the content of the metallic iron is less than or equal to 50 ppm.
4. A method for preparing a carrier material, characterized in that: The steps include: Providing a porous carbon material; The porous carbon material is subjected to oxidation treatment to obtain the carrier material; wherein the carrier material has a plurality of pores; The total oxygen content of the carrier material is Ot, and the mass percentage of Ot in the carrier material is 0.2%-10.0%; The extra-pore oxygen content of the carrier material is Os, and the mass ratio of the Os to the Ot is (0.1-0.5):
1.
5. The preparation method according to claim 4, characterized in that: The oxidation treatment step specifically includes: The porous carbon material is subjected to oxygen filling treatment in an oxidizing gas atmosphere to obtain an oxygen-filled material; The oxygen-filled material is subjected to a heat treatment under an inert gas purge to obtain the carrier material.
6. The preparation method according to claim 5, characterized in that: The oxidizing gas comprises oxygen; and / or The gas flow rate of the oxidizing gas is 20 mL / min-40 mL / min; and / or The filling time of the oxygen filling treatment is 0.5h-4h; and / or The temperature of the oxygen filling treatment is 20°C-30°C; and / or The inert gas comprises nitrogen and / or argon; and / or The gas flow rate of the inert gas is 10 mL / min-50 mL / min; and / or The temperature of the heating treatment is 200°C-500°C; and / or The heating treatment time is 0.5h-2h.
7. The preparation method according to claim 6, characterized in that: The filling time is 2h-3h; and / or The gas flow rate of the inert gas is 10 mL / min-30 mL / min; and / or The heating treatment time is 0.5h-1.5h.
8. The preparation method according to claim 4, characterized in that: The oxidation treatment step specifically includes: Dispersing the porous carbon material in a nitric acid solution to obtain a first mixed solution, and drying the first mixed solution at a low temperature to obtain a porous carbon material adsorbed with nitric acid; dispersing the porous carbon material adsorbed with nitric acid in an oxidizing solution to obtain a second mixed solution; The second mixed solution is subjected to heating treatment, washing, and drying to obtain the carrier material.
9. The preparation method according to claim 8, characterized in that: The temperature of the low temperature drying is 40°C-80°C; and / or The concentration of the nitric acid solution is 1.0 mol / L-8.0 mol / L; and / or The mass percentage of the porous carbon material in the first mixed solution is 20%-60%; and / or The oxidizing solution comprises at least one of a nitric acid solution, a sulfuric acid solution and a hydrogen peroxide solution; and / or The mass percentage of the porous carbon material adsorbed with nitric acid in the second mixed solution is 0.1%-2.0%; and / or In the step of heating the second mixed solution, the temperature of the heating treatment is 70° C.-100° C., and / or the time of the heating treatment is 1 h-6 h; and / or The step of heating, washing and drying the second mixed solution specifically comprises: heating the second mixed solution to obtain a third mixed solution; Performing solid-liquid separation on the third mixed solution, and washing the product obtained by solid-liquid separation with water until the pH value is 3-7; The washed product is dried to obtain the carrier material, wherein the drying is freeze drying, the freeze drying temperature is -45°C to 0°C, and / or the freeze drying vacuum degree is 0.1Pa-2.5Pa, and / or the freeze drying heating rate is 45°C / min-25°C / min.
10. The preparation method according to claim 9, characterized in that: The concentration of the nitric acid solution is 2.0 mol / L-4.0 mol / L; and / or The mass percentage of the porous carbon material in the first mixed solution is 40%-50%; and / or The oxidizing solution is a nitric acid solution, and the concentration of the nitric acid solution is 0.2 mol / L-2.0 mol / L; and / or The mass percentage of the porous carbon material adsorbed with nitric acid in the second mixed solution is 0.5%-1.0%; and / or In the step of heating the second mixed solution, the temperature of the heating treatment is 70° C.-80° C., and / or the time of the heating treatment is 2 h-4 h; and / or The third mixed solution is subjected to solid-liquid separation, and the product obtained by the solid-liquid separation is washed with water until the pH value is 4-6.
11. The preparation method according to claim 4, characterized in that: The oxidation treatment step specifically includes: The porous carbon material is subjected to oxygen filling treatment in an oxidizing gas atmosphere to obtain an oxygen-filled material; Heat-treating the oxygen-filled material under an inert gas purge to obtain an oxygen-containing porous carbon material; Dispersing the oxygen-containing porous carbon material in a nitric acid solution to obtain a first mixture, and drying the first mixture at a low temperature to obtain an oxygen-containing porous carbon material adsorbed with nitric acid; dispersing the oxygen-containing porous carbon material adsorbed with nitric acid in an oxidizing solution to obtain a second mixture; The second mixture is subjected to a heating treatment, washed, and dried to obtain the carrier material.
12. A catalyst, characterized in that The catalyst comprises the support material according to any one of claims 1 to 3 or a support material prepared by the method according to any one of claims 4 to 11.
13. A membrane electrode, characterized in that: The membrane electrode comprises the support material as claimed in any one of claims 1 to 3 or the support material prepared by the method as claimed in any one of claims 4 to 11, or comprises the catalyst as claimed in claim 12.
14. A fuel cell, characterized in that: The fuel cell comprises the support material as claimed in any one of claims 1 to 3 or the support material prepared by the method as claimed in any one of claims 4 to 11, or comprises the catalyst as claimed in claim 12, or comprises the membrane electrode as claimed in claim 13.
15. An electrical equipment, characterized in that: The electrical equipment comprises a carrier material as described in any one of claims 1 to 3 or a carrier material prepared by the method as described in any one of claims 4 to 11, or comprises a catalyst as described in claim 12, or comprises a membrane electrode as described in claim 13, or comprises a fuel cell as described in claim 14.
Citation Information
Patent Citations
Method of preparing mesoporous carbon material and application of mesoporous carbon material as noble metal catalyst carrier
CN103011125A
Pt-Nafion / C catalyst and preparation method and application for same
CN103120960A
A kind of preparation method of carbon supported platinum electrocatalyst for fuel cell
CN106961831B
Catalyst-carrier carbon material, solid-polymer fuel cell catalyst, solid-polymer fuel cell, and method for manufacturing catalyst-carrier carbon material
CN107431212A
Modified activated carbon and its manufacturing method
CN110582464A